1994
DOI: 10.1136/gut.35.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory small intestinal motility in 'diarrhoea' predominant irritable bowel syndrome.

Abstract: Dysmotility of the duodenum and proximal jejunum has been reported in patients with irritable bowel syndrome. This study extended these findings by recording fasting ambulatory motility from electronic strain gauge sensors sited in the jejunum and ileum of eight diarrhoea predominant irritable bowel syndrome patients and 12 healthy controls. During the day, periodicity of migrating motor complexes mean (SEM) did not differ between patients (92 (10) min) and controls (85 (7) min). At night, periodicity was shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 37 publications
5
69
1
Order By: Relevance
“…They can be induced by cholecvstokinin or prostigmine in a proportion of both IBS patients and controls to a similar extent [2], A temporal relation of prolonged propagated contractions to abdominal pain was reported in 61% of IBS patients, but in only 17% of controls [1]. Again, this finding could not be corroborated in a subsequent careful study [5], Clustered contractions are groups of propagated smallintestinal contractions of approximately 1 min duration, occurring every other minute. Therefore they are also called 'minute rhythm'.…”
mentioning
confidence: 41%
“…They can be induced by cholecvstokinin or prostigmine in a proportion of both IBS patients and controls to a similar extent [2], A temporal relation of prolonged propagated contractions to abdominal pain was reported in 61% of IBS patients, but in only 17% of controls [1]. Again, this finding could not be corroborated in a subsequent careful study [5], Clustered contractions are groups of propagated smallintestinal contractions of approximately 1 min duration, occurring every other minute. Therefore they are also called 'minute rhythm'.…”
mentioning
confidence: 41%
“…5±7 This is also relevant in view of the altered patterns of motility which can be observed in patients with irritable bowel syndrome during prolonged recordings from the small intestine, 8±10 although other studies have not observed such alterations. 11,12 The aims of this study were therefore to compare, utilizing an ambulant recording technique, the effects of a 24-h oral dose regimen of cisapride on interdigestive and post-prandial motor activity of the proximal small intestine in irritable bowel syndrome patients with predominant constipation, irritable bowel syndrome patients with predominant diarrhoea and healthy subjects. In each group a control (placebo) period of recording was undertaken, while separate groups of healthy subjects and of irritable bowel syndrome patients, who were studied in similar fashion but without the drug, acted as additional control groups.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of agreement regarding the aetiology and physiology of IBS, but theories include abnormal gastrointestinal motor function, [24][25][26] enhanced visceral perception, 27-29 the influence of psychosocial factors such as a history of childhood abuse, 30 genetic predisposition [31][32][33] and a possible role for enteric mucosal inflammation 34 such as that precipitated by acute bacterial gastroenteritis. 35 To date, studies on the aetiology of IBS have been descriptive or retrospective and longitudinal studies are needed to clarify matters.…”
Section: (See Boxes 1 and 2)mentioning
confidence: 99%